2023
DOI: 10.3389/fpsyg.2022.1022914
|View full text |Cite
|
Sign up to set email alerts
|

A multidimensional construct of helicopter parenting and college students’ game and social media addictive behaviors: A cross-cultural study in South Korea and China

Abstract: IntroductionWe explored latent classes of helicopter parenting among Korean and Chinese college students. In addition, we examined whether these latent classes of helicopter parenting are related to Korean and Chinese students’ game and social media addictive behaviors.MethodsA three-step latent class analysis was conducted using 452 students from six universities in South Korea and 372 students from four universities in China.Results and discussionWe identified four distinct helicopter parenting latent classe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…For example, “I think it’s easy for me to keep my body attractive.” The scale uses a 4-point scoring system, with 1 being “strongly disagree” and 4 being “strongly agree.” A higher score indicates a higher level of physical self-esteem among college students. In the original validation study by Fox and Corbin ( 37 ), the Cronbach’s α coefficient was reported as 0.92, and the Cronbach’s α coefficient of this study is 0.967, indicating a consistent reliability across different contexts.…”
Section: Methodsmentioning
confidence: 49%
See 2 more Smart Citations
“…For example, “I think it’s easy for me to keep my body attractive.” The scale uses a 4-point scoring system, with 1 being “strongly disagree” and 4 being “strongly agree.” A higher score indicates a higher level of physical self-esteem among college students. In the original validation study by Fox and Corbin ( 37 ), the Cronbach’s α coefficient was reported as 0.92, and the Cronbach’s α coefficient of this study is 0.967, indicating a consistent reliability across different contexts.…”
Section: Methodsmentioning
confidence: 49%
“…In the original validation study by Fox and Corbin (37), the Cronbach's α coefficient was reported as 0.92, and the Cronbach's α coefficient of this study is 0.967, indicating a consistent reliability across different contexts.…”
Section: Physical Self-esteemmentioning
confidence: 50%
See 1 more Smart Citation